Constructing Sonic Heritage: The Accumulation of Knowledge in the Context of Sound Archives - Johannes Müske (Journal of Ethnology and Folkloristics)
This paper argues that sonic heritage does not exist per se, but is socially constructed. rather it arises from various measures of accumulating knowledge with respect to the collected sounds. a variety of actors, for example, scholars, or foundations, participate in this process by editing parts of the collections, publishing ethnographic or historic studies, and conducting digitisation projects. In this context, sound collections are identified as ‘cultural heritage’ as a consequence and result of archival practices. The processes that are linked to cultural heritage will be outlined and discussed in the present research in line with the model of the social construction of technology (SCOT). More specifically, the social construction of sonic heritage will be illustrated with a case study on the Edison-cylinders collection in the Berlin Phonogramm-archiv, UNESCo Memory of the world since 2000.